DETERMINATION OF FINANCIAL LITERACY THROUGH FINANCIAL KNOWLEDGE AND FINANCIAL ATTITUDE TOWARDS THE FINANCIAL MANAGEMENT OF UMKM BUSINESSES IN PARI CITY VILLAGE, PANTAI CERMIN DISTRICT, SERDANG BEDAGAI REGENCY - Sari, Maya Macia; Sari, Pipit Buana; Pohan, Syahrial Hasanuddin (Proceeding International Conference of Science Technology and Social Humanities; Vol 1 (2022): International Conference of Science Technology and Social Humanities, 2022)
This study aims to determine  and analyze the influence of financial literacy through financial knowledge and financial attitude on the financial management of UMKM in Pari City Village, Pantai Cermin District, Serdang Bedagai Regency. The benefits of this research for the community of UMKM actors  are expected to increase  scientific knowledge in the field of financial management, especially managing UMKM finances. This research is an associative study  with a total sample of 30 UMKM actors. The type of  data used in this study is primary data, namely by conducting interviews and questionnaires using  the likert measurement scale. The data analysis technique of this study used  multiple linear regression analysis with the SPSS version 25 program. The results of this study show that partially and simultaneously the variables of financial knowledge  and financial attitude have a positive and significant effect on financial management.  The percentage of influence of these variables is 70.9%.